Model study of coexistence of Jahn-Teller distortion, antiferromagnetism and superconductivity in iron pnictide superconductors. (December 2016) - Pradhan, B.; Goi, S.K.; Behera, Srikanta; Parida, P.K.; Mishra, R.N.
Abstract: We have proposed a theoretical model for the coexistence of superconductivity (SC), antiferromagnetism (AFM) and Jahn-Teller (JT) effect in the mean field approximation for iron based superconductors. The model is solved by using Zubarev's double-time Green's function technique to get their selfconsistent gap equations. Then these gap equations are solved numerically. Abstract : Highlights: A Hamiltonian for Fe based SCs with SC, AFM and JT interactions is proposed. Zubarev's technique of double time Green's functions is used for calculations. The interplay of three gap parameters are studied. The gap values shows strong dependence on one another.